The effects of coaching techniques on well-being of digital-technology users - Marisa Phaekwamdee; Smitti Darakorn Na Ayuthaya; Supaporn Kiattisin (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
As digital technology has become indispensable, its overuse has resulted in mental health issues for many users. While it benefits people by providing fast and plentiful information, it also creates sadness, anxiety, and stress. This study aimed to assess the well-being of digital technology users before, during, and six months after attending a coaching session that was designed according to the International Coaching Federation (ICF) approach. Seligman's well-being model, consisting of positive emotion, engagement, relationships, meaning, and accomplishment (PERMA), was applied for the measurement, and then analyzed with descriptive statistics, repeated ANOVA, and paired-sample t-tests. The findings showed that coaching techniques can enhance well-being and that their results were maintained for six months after participation. In conclusion, coaching techniques should be promoted as a procedure for improving the well-being of digital technology users who face mental health issues.
Keywords: 650; coaching; digital technology users; GROW model; ICF; PERMA model; well-being